Rol del banco de Pichincha y cooperativa padre Julian Lorente; en los procesos de centralización del capital en los sectores construccion y actividades inmobiliarias, empresariales y de alquiler en el cantón Loja - Calderón Tinizaray, Diana (2011)
This research was conducted in the city of Loja, whose theme is: "ROLE OF BANCO DE PICHINCHA AND COOPERATIVA PADRE JULIAN LORENTE; IN THE PROCESS OF CENTRALIZATION OF CAPITAL IN THE SECTORS OF CONSTRUCTION AND REAL ESTATE, RENTING AND BUSINESS DEL CANTON LOJA "information that was obtained from the same financial institutions and entities such as the Superintendency of Banks and the Superintendency of Companies. With the results obtained by the two organizations studied, we can identify which abstractions are higher than loans resulting in a capitalization of land at a rate of 3.06 on average, this capitalization is given in the Bank of Pichincha since their funds collected are not used in full for loans within the canton. Comparing the cooperative bank and the time spent in the market, the cooperative who is set longer than 43 years while the bank 6 years, although this is the bank that has the highest number of customers that the year 2006 was 26 500 increase for 2009 to 29 800, while in the cooperative in 2006 was 16 900 partners to increase for 2009 to 19 600, and secondly in terms of both the bank and loans cooperative resources have been allocated to consumer loans at a higher rate shown by the 74.68% by the cooperative, and 20.70% by the bank.On the other hand when analyzing business structures, these are running through family ties, since they are shareholders of companies who manage and run companies, in what has to do with the assets they own has increased by part of the construction sector where in 2005 was 177 and average $ 509.39 for 2009 totaled 219.10 348 dollars on average, in real estate and rental business for 2005 is 36 dollars on average 858.15 , increasing from 2009 to 113 for the average $ 272.39, and increase their capital also increased its obligations, as it is for the construction sector in 2005 was 128 average $ 294.02 which was increased in 2009 to 220 average $ 846.85, and for real estate and rental business in 2005 is 28 dollars on average 873.07 experiencing an increase of 104 for 2009 average $ 544.75. Finally, the hypothesis is proved to be, a modest business development due to continued growth in sectors, equity and administrative links, concentrating resources in fewer hands, further exacerbating the capitalization of the territory by the Bank of Pichincha.